Leituras de Medeia: o mito e o lastro cultural - Leites Junior, Pedro (2012)
If the classical text is an equivalent to the universe and reverberates as background in the collective unconscious, as stated by Ítalo Calvino (2002), is through the rereading processes, through intertextuality that the text will revive over time. The intertextual work, however, as shown by Laurent Jenny (1979), can reveal itself in the reactivation of meanings of the first work as much as show itself on the resignation or deconstruction of the opposite discourse. Thus, starting from the dialectic between present and past, contemporary and ancient, observing the potential artistic language of conscious rescue of a past discourse, taken (or not) as truth , and the possibility of reconstruction of meanings and elaboration of new aesthetics, this study has the objective of developing a comparative and interpretative research, from a group of literary, dramaturgic and artistic works produced in different historical contexts, which dialogue with the Greek myth of Medea. We have interest in observing and interpreting how, in the mimetic process and according to the cultural ballast, the mimemes realize the transposition of the myth; developing a study that involves considering if there was or if there is a differential effect in the process of transposition of the language that catches a content, a configuration of the myth; verifying in what extent content and aesthetical form are maintained and which works present a rupture to the narrative series around the myth of Medea. In this perspective, we intend to reflect about the way artists, writers and playwrights have aesthetically re-appropriated works from the past to realize the questioning of the present time or of their historical temporality, from new artistic creations that proceed out of the myth of Medea. In this sense, our study starts from the mythical narrative of the Argonauts to proceed with readings of the classics: Medea (431 b.C.), by Euripides, Medea (n.d.), by Seneca, Médée (1635), by Pierre Corneille. These narratives are here placed in dialogue with a cutting of images, covering a cultural ballast of pictographic representations of the myth of Medea, to which we have added the filmic narratives of Medea (1969), by Pier Paolo Pasolini, and Medea (1988), by Lars Von Trier. In a dialogical perspective with the theme and the myth of Medea there have been chosen the texts of the Brazilian drama Gota d água (1975), by Chico Buarque and Paulo Pontes, and Des-medeia (1995), by Denise Stoklos, which are also part of our corpus of research, in order to verify how the myth is represented in the contemporary Brazilian context, more specifically on how the referential ballast is read by the writer subjects Chico Buarque, Paulo Pontes and Denise Stoklos, representatives of a collectivity to which the writer and playwright take part as intellectuals.